The Millennial Fathers' Role in Parenting between Tradition and Equality: Peran Ayah Milenial dalam Pengasuhan antara Tradisi dan Kesetaraan - Tisya Permatasari; Astri Chintya Astana (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Traditional patriarchal norms in Indonesian society have long dictated gendered parenting roles, positioning fathers primarily as providers. Specific Background: However, since the early 2000s, digitalization, shifting family structures, and national gender equality discourse have catalyzed changes in paternal involvement. Knowledge Gap: Despite increasing awareness, few studies comprehensively explore how Indonesian millennial fathers reconcile traditional masculinity with modern parenting expectations in diverse cultural contexts. Aims: This study investigates the evolving parenting roles of millennial fathers amid the cultural tension between traditional norms and contemporary gender equality values. Results: Findings indicate a significant increase in fathers’ emotional and physical engagement in child-rearing, though role strain persists due to lingering patriarchal pressures and inadequate policy support. Novelty: This study offers a nuanced synthesis by integrating sociological and psychological perspectives, mapping out identity negotiations, and examining structural and cultural enablers and barriers for millennial fathers. Implications: The research highlights the necessity for structural reforms and inclusive policy frameworks that support father involvement as a norm, thereby advancing equitable family dynamics and child well-being within Indonesia’s shifting sociocultural landscape.Highlight : Millennial fathers in Indonesia are increasingly involved in emotional and daily caregiving, negotiating between traditional masculinity and modern egalitarian ideals. Role strain often emerges due to conflicting expectations between cultural norms and evolving gender roles. Social media and national policies play a vital role in supporting and reshaping paternal engagement in childcare. Keywords : Millennial Fathers, Parenting Roles, Gender Equality, Patriarchal Culture, Role Strain